Comparative Study on Plant Growth Promotion by Endophytic Pseudomonas Spp. and Bacillus Spp. of Solanum Lycopersicum - Mishra, Sampada; Mahato, Saroj Kumar; Basi, Sabin; Basi-Chipalu, Shradha (International Journal of Applied Sciences and Biotechnology, 2017)
Minimization of deleterious effects of chemical fertilizers on health, ecosystem and economy can only be achieved by finding healthy, eco-friendly and cheap alternatives. Naturally selected symbiotic relationship between the endophytic bacteria and their host plants makes them an ideal candidate as biofertilizer. They can synthesize various plant growth hormones as well as assist their host in uptake of nutrients from soil. The study was designed to compare plant growth promotion of Solanum lycopersicum by Bacillus spp., Pseudomonas spp. and total endophytic community isolated from roots of S. lycopersicum, grown in the soil samples collected from various locations of Kathmandu valley of Nepal. Tomato seeds were inoculated with mixtures of eight endophytic strains of Bacillus spp. and Pseudomonas spp., and crude endophytes obtained from each location separately. Endophytic treatments, except Pseudomonas spp., inhibited seminal root growth during 12-days germination period. However, after plantation, root and shoot biomass was enhanced by the endophytes, with no significant differences among the bacterial treatments. The shoot height was also enhanced, among which Pseudomonas spp. had the strongest effect. In phosphate solubilization assay, out of seventy-two isolates each of Bacillus spp. and Pseudomonas spp. tested, twenty-four isolates of Pseudomonas spp. and sixteen isolates of Bacillus spp. could solubilize phosphate. Higher number of phosphate solubilizing isolates of Pseudomonas spp. might provide a possible explanation for the greater enhancement of shoot height by Pseudomonas spp. as compared to Bacillus spp. Int J Appl Sci Biotechnol, Vol 4(4): 464-469